PENDAMPINGAN PEMBUATAN PENELITIAN TINDAKAN KELAS (PTK) GUNA PENINGKATAN PANGKAT GURU DI SMA NEGERI 10 DENPASAR - Rulianto; Lianda Dewi Sartika; Sri Datuti; Ida Bagus Brata (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Classroom action research (PTK) is one of the requirements for teacher promotion. However, many teachers have difficulty designing and implementing PTK. The purpose of this service is to provide assistance to teachers in creating and implementing PTK in order to fulfill the requirements for promotion. The approach used is direct assistance to teachers who need assistance in designing and implementing PTK. During the mentoring process, ongoing evaluation, feedback and discussions are carried out between the mentor and the teacher being mentored. Initial results show an increase in the quality of PTK design and implementation after receiving assistance. Teachers become more aware of the procedures and techniques for preparing PTK. It is hoped that in the future this assistance can continue to be carried out to increase teacher competence in making PTK as one of the requirements for promotion.